On Ramsey (3K_2,2K_5)-Minimal Graphs - Permataputri, Nailul Yuni (Pendidikan Matematika, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2024)
For given two graphs G and H, the notation F?(G,H) means that any red-blue coloring of all the edges of F contains a red copy of G as a subgraph or a blue copy of H as a subgraph. A graph F is Ramsey (G,H)-minimal if F?(G,H) and for any edge e in F then F-e?(G,H). The class of all (G,H)-minimal graph, is denoted by R(G,H). In this research, we determined graphs in R(3K2,2K5 ).